2019
DOI: 10.1002/rnc.4500
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and robust adaptive iterative learning control of a vehicle‐based flexible manipulator with uncertainties

Abstract: Summary In this brief, this paper deals with a robust adaptive iterative learning control (ILC) problem for a flexible manipulator attached to a moving vehicle with uncertainties. To begin with, considering the infinite dimensionality of the flexible distributed parameter system, a coupled ordinary differential equation and partial differential equation model is established without any discretization. Then, it is followed by a presentation of an adaptive ILC strategy, which can drive the vehicle and joint to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…In essence, flexible manipulator is a distributed parameter system, which can be accurately described by partial differential equations (PDEs). Different control schemes have been developed for flexible systems based on PDEs, such as adaptive fault-tolerant control (Zhang et al, 2019b), boundary control (He et al, 2017; Liu et al, 2017; Xing and Liu, 2019b), disturbance observer design (Yang and Liu, 2019), robust adaptive iterative control (Xing and Liu, 2019a). In the design of these controllers, the problem of the capacity of the communication channel during the transmission of the input signal is not considered, and signals need to be delivered from time to time, which will increase the communication burden and even affect the performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In essence, flexible manipulator is a distributed parameter system, which can be accurately described by partial differential equations (PDEs). Different control schemes have been developed for flexible systems based on PDEs, such as adaptive fault-tolerant control (Zhang et al, 2019b), boundary control (He et al, 2017; Liu et al, 2017; Xing and Liu, 2019b), disturbance observer design (Yang and Liu, 2019), robust adaptive iterative control (Xing and Liu, 2019a). In the design of these controllers, the problem of the capacity of the communication channel during the transmission of the input signal is not considered, and signals need to be delivered from time to time, which will increase the communication burden and even affect the performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…After more than 30 years of development, ILC has been widely used in the tracking and control of intelligence systems, we can refer to References 2‐9 and the references therein. Recently, ILC has made relevant achievements in modeling a flexible manipulator, 10 self‐learning robust control synthesis and tracking design of general uncertain dynamical systems, 11 self‐learning optimal regulation for event‐driven discrete nonlinear systems, 12 and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to real-time-feedback and/or feedforward control techniques, many case studies of ILC have shown a substantial reduction in tracking error. Relevant applications include robotassisted stroke rehabilitation 1 , high speed train control 2 , laser additive manufacturing 3 , and vehicle-mounted manipulators 4 , all of which use nonlinear models. In fact, while the majority of ILC literature focuses on linear systems, the prevalence of nonlinear dynamics in real-world systems has motivated the development of numerous ILC theories for discrete-time nonlinear models [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%